A study of arabic language learning challenges among students in higher education institution / Abd Rahman Jamaan - Jamaan, Abd Rahman (UiTM Cawangan Johor, 2025)
This paper explores the challenges of learning Arabic as a third language for students at higher education institution. The study identified three main issues that affect learning outcomes: language challenges, motivation barriers and support level. The phonological, grammatical, and sociocultural complexity of the Arabic language poses major obstacles. This is especially true for students who have limited access to specific aspects of the language. The same is true for motivational factors. Where students' perceptions of the relevance of the Arabic language influence their participation, limited educational support also exacerbates these problems. The research used a quantitative method using surveys to measure students' perceptions and experiences with these challenges. The results suggest that although phonological and grammatical problems significantly impact performance, motivational support and tailored teaching methods can alleviate some of these barriers. The study highlights the potential of technology-based learning and interactive learning approaches, such as task-based communication methods, to improve Arabic language learning outcomes at higher education institution. The research suggests that these strategies can be integrated with Arabic language courses to increase participation and reduce barriers to language learning.